Situation Report: Romania, 7 March 1973 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Changes in the Front of Socialist Unity Ceausescu's New Counselors Law on National Defense and Domestic Armament Production Priorities in Foreign Trade Nuclear Research Reactor for Romania (II) Foreign Economic Relations